2016
DOI: 10.5194/wes-1-129-2016
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the wake deflection downstream of a wind turbine in different atmospheric stabilities: an LES study

Abstract: Abstract. An intentional yaw misalignment of wind turbines is currently discussed as one possibility to increase the overall energy yield of wind farms. The idea behind this control is to decrease wake losses of downstream turbines by altering the wake trajectory of the controlled upwind turbines. For an application of such an operational control, precise knowledge about the inflow wind conditions, the magnitude of wake deflection by a yawed turbine and the propagation of the wake is crucial. The dependency of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 36 publications
9
109
1
Order By: Relevance
“…Thus, the axial and tangential velocity at the rotor disk U n and U t are selected as the unknown parameters instead of a and a [31][32][33]. In this study, a coupled approach is adopted for the ADM-R Energies 2018, 11, 665 6 of 24 model in the yawed condition, in which U n and U t are directly obtained from the CFD simulation result of local velocities on the rotor disk U x , U y , U z by using the following transformation:…”
Section: = Cosmentioning
confidence: 99%
“…Thus, the axial and tangential velocity at the rotor disk U n and U t are selected as the unknown parameters instead of a and a [31][32][33]. In this study, a coupled approach is adopted for the ADM-R Energies 2018, 11, 665 6 of 24 model in the yawed condition, in which U n and U t are directly obtained from the CFD simulation result of local velocities on the rotor disk U x , U y , U z by using the following transformation:…”
Section: = Cosmentioning
confidence: 99%
“…One promising concept is the wake deflection by intentional yaw misalignment of single wind turbines. The principle of deflecting the velocity deficit behind a wind turbine was observed in field measurements by Trujillo et al (2016), in wind tunnel experiments (e.g., Medici and Alfredsson, 2006;Krogstad and Adaramola, 2012) and in numerical simulations (e.g., Jiménez et al, 2010;Gebraad et al, 2014;Vollmer et al, 2016). Further, Gebraad et al (2014) and Fleming et al (2016) applied the concept to wind farm control strategies using large-eddy simulation (LES) methods, showing a potential power increase in wind farm applications.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Gebraad et al (2014) and Fleming et al (2016) applied the concept to wind farm control strategies using large-eddy simulation (LES) methods, showing a potential power increase in wind farm applications. Vollmer et al (2016) report on an asymmetric deflection of a turbine's wake with respect to its direction of yaw misalignment in numeric studies. Similarly, Bastankhah and Porté-Agel (2016) found that a wake moves upwards or downwards depending on the direction of a yaw misalignment using PIV (particle image velocimetry) measurements behind a small turbine model.…”
Section: Introductionmentioning
confidence: 99%
“…From the averaged flow, a power is computed, which would have been produced by an additional hypothetical at some point downstream. This approach was adapted from power calculations used in Vollmer et al (2016) This power is computed by averaging the cubed wind speed over a hypothetical rotor disk from the averaged flow. The cubed average is then converted to power through…”
Section: Methodsmentioning
confidence: 99%
“…In Vollmer et al (2016), largeeddy simulations (LES) are used to study the behavior of wake steering under varying atmospheric conditions. The authors note that the shape of the wake under yawed conditions is curled rather than circular.…”
mentioning
confidence: 99%